2022
DOI: 10.1111/infi.12412
|View full text |Cite
|
Sign up to set email alerts
|

Global financial crisis versus COVID‐19: Evidence from sentiment analysis

Abstract: This study examines the relationship between sentiment and the realized volatility of returns for different asset classes (stocks, bonds, foreign currency, and commodities). Specifically, we aim to answer two key questions: first, how does sentiment relate to volatility during crises (mainly during the global financial crisis [GFC] and the COVID‐19 pandemic)? Second, can sentiment be used to forecast volatility during crises? Using two nonparametric methods, mutual information and transfer entropy, we find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…As a consequence, this pandemic has caused large disruptions in labor supply (thus affecting supply chains) (Guerrieri et al 2020 ), in the tourism industry (Sharma and Nicolau 2020 ) and in international trade (Gruszczynski 2020 ). Therefore, despite some observed increases in the flow of information (Maghyereh and Abdoh 2022 ), like previous global shocks (Fig. 3 ), the COVID-19 pandemic caused an overall reduction in global interconnectedness (Shrestha et al 2020 ).…”
Section: Effects Of the Covid-19 Pandemic On Global Interconnectednessmentioning
confidence: 69%
See 2 more Smart Citations
“…As a consequence, this pandemic has caused large disruptions in labor supply (thus affecting supply chains) (Guerrieri et al 2020 ), in the tourism industry (Sharma and Nicolau 2020 ) and in international trade (Gruszczynski 2020 ). Therefore, despite some observed increases in the flow of information (Maghyereh and Abdoh 2022 ), like previous global shocks (Fig. 3 ), the COVID-19 pandemic caused an overall reduction in global interconnectedness (Shrestha et al 2020 ).…”
Section: Effects Of the Covid-19 Pandemic On Global Interconnectednessmentioning
confidence: 69%
“…When a shock occurs, peri- and telecoupling processes (e.g., trade, tourism) are disrupted, thus, the social, economic and environmental consequences of the shock tend to be more drastic in highly interconnected systems than in those that are more isolated. In addition, due to the disruption of the movement of people and materials, over the short and medium terms there may be a tendency for the magnitude of telecoupling to decline [although some telecouplings, particularly those related with the flow of information, may actually increase (Maghyereh and Abdoh 2022 )], while the magnitude of intracouplings may increase (e.g., low availability of global commodities induces reductions in consumption and/or shifts to locally produced commodities). In addition, the magnitude of pericouplings may increase, as geographically closer suppliers start to fill the void left by geographically distant suppliers, even though such outcome is context dependent given the different conditions needed for supply chain formation (Jayaram et al 2004 ) (Fig.…”
Section: Impacts Of Global Shocks On Metacoupled Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have shown that measuring sentiment and attention to an ongoing phenomenon and subsequently using those measures in volatility models can significantly improve our understanding of market behavior. The effects of attention and sentiment are amplified for unexpected and highly impactful events, whether it be the recent COVID-19 pandemic (Chen et al, 2020;Lyócsa et al, 2020a;Smales, 2021;Wang et al, 2021;Maghyereh and Abdoh, 2022),…”
Section: Introductionmentioning
confidence: 99%